The co-ordinative practices of temporary organisations - Peters, Linda D.; Pressey, Andrew D. (Emerald, 2016)
Purpose: This paper aims to explore the necessary mechanisms for coordination in complex industrial networks which are temporary in nature, known as temporary organisations (TOs). Design/methodology/approach: The paper is based on two in-depth case studies conducted in the UK construction industry. Findings: The paper outlines the necessary mechanisms for coordination in TOs – referred to as “scaffolding practices” – which ensure consistency(stability in terms of thinking and action), consensus (agreement) and co-constitutiveness (personal pledges and commitments). Research limitations/implications: The study provides practical implications for situations where actors create temporary organisational specific logics. This “logic” helps explain how actors are able to undertake tasks of finite duration where members lack familiarity and have competing loyalties. Originality/value: The paper is novel in that it represents the first extant attempt to examine “temporary industrial organizations” where individuals from different (often competing) organisations collaborate on a task for a defined period and suggests how coordination may be achieved.